ANALISIS POTENSI EKONOMI SEBAGAI PENUNJANG PERTUMBUHAN EKONOMI YANG PESAT - Akher Juhafa; Ziarmal Raqim (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2023)
In supporting strategic sectors in Surakarta City, it is necessary to have a link between these sectors, one of which is roads. The road is a means of transportation that connects one place to another. Roads have a fairly important role in the distribution and expedite the wheels of the economy. The road is one of the supporting transportation facilities that is most often used by the majority of the community, so that it greatly influences the daily activities of the community. In Law no. 38 of 2004 concerning roads states that roads are transportation infrastructure that play an important role in the economic, social, cultural, environmental, political and defense security fields.